Comparative evaluation of lead emissions and toxicity potential in the life cycle of lead halide perovskite photovoltaics. (1st January 2019) - Billen, Pieter; Leccisi, Enrica; Dastidar, Subham; Li, Siming; Lobaton, Liliana; Spatari, Sabrina; Fafarman, Aaron T.; Fthenakis, Vasilis M.; Baxter, Jason B.
Abstract: Lead halide perovskites (LHP) are an emerging class of photovoltaic (PV) materials that have drawn intense interest due to their power conversion efficiencies above 23% and their potential for low-cost fabrication. However, the toxicity of lead causes concern about its use in LHP-PV at large scales. Here, we quantified lead intensity and toxicity potential of LHP-PV in potential commercial production. Lead intensity in LHP-PV life cycles can be 4 times lower and potential toxic emissions can be 20 times lower than those in representative U.S. electricity mixes, assuming that PV operational lifetimes reach 20 years. We introduce the metric "toxicity potential payback time", accounting for toxic emissions in the life cycle of energy cycles, and showed that it is < 2 years for perovskite PVs produced by and displacing the same grid mix. The toxicity potential associated with the energy of manufacturing a PV system dominates that associated with release of embodied lead. Therefore, the use of lead should not preclude commercialization of LHP-PVs. Instead, effort should focus on development of low-energy manufacturing processes and long service lifetimes. Additional detailed investigations are needed to quantify the full life cycle of commercial production of perovskites and to minimize potential emissions. Graphical abstract: Image 1 Highlights: Quantified lead intensity, toxicity potential of lead halide perovskite PV. Toxicity potential from embodied energy much greater than from release of lead. Perovskite PV has lower lead intensity and toxicity potential than grid electricity. Toxicity potential payback time <2 years for perovskite PV.